Examining the association between parenting stress and the development of early childhood caries - Tang C, Quinonez RB, Hallett K, Lee JY, Whitt JK. (Blackwell Synergy, 2005)
Numerous studies have explored the effects of pediatric health on parenting stress, but very little work has been carried out to explore the opposite and equally as compelling relationship of how parenting stress might affect child health, especially as it relates to oral health.